Higher Education of Latin America in the Trajectory of International Student Mobility - E. G. Ermolieva (Высшее образование в России)
Latin America and Caribbean Region (LAC), with a student enrollment about 30 million, has its own space in the global inter-university exchange. And the article aims to observe current trends and specific features of the internationalization of LAC higher education systems. The author analyzes different models of interaction of the region, firstly, with the countries of the global “North”, secondly, in the “South-South” format, and in a trilateral model  – “North-South-South”. Also, the article studies some versions of intraregional cooperation in South America, as well as the Network university consortium (BRICS as example). The research exposes a new trend, the participation of LAC countries in the virtual student mobility, which has become a “new normal” during the  pandemic  period  and  has  retained  its  significance  at  the  present  time.  A  special  place  is  given to  Russian-Latin  American  cooperation  which  has  a  long  history.  Additionally,  the  opportunities and difficulties of this bi-regional partnership in the higher education sphere at the present time are analyzed.Despite  the  fact  that  the  Latin  American  region  lies  somewhat  away  from  the  main  routes  of global interuniversity exchange, it is gradually increasing its share in the flow of mobile students by active participation in triangle formats. Simultaneously, the region develops new options for intra-regional cooperation to increase the competitiveness of Latin American universities in the international education market.